Identification of Main Oyster Species and Comparison of Their Genetic Diversity in Zhejiang Coast, South of Yangtze River Estuary - Liu, Sheng; Xue, Qinggang; Xu, Hongqiang; Lin, Zhihua (Frontiers in Marine Science, 2021)
Oysters are an important aquaculture species distributed worldwide, including in Zhejiang Province located on the east coast of China. Because of the high diversity and complicated introduction history of oysters and their seedlings, there have been much disagreement about each species origin, and the dominant and indigenous species are not yet clear. We sampled 16 batches of oysters from seven sites in three aquaculture bays and found two main oyster species: Crassostrea sikamea and Crassostrea angulata; the former occupied the higher intertidal zone and comprised more than 70% of the cultured oysters. Based on the cytochrome oxidase C subunit I (COI) and mitochondrial noncoding region (MNR), C. sikamea showed higher genetic diversity than C. angulata. For these species, the analysis of molecular variance among COI sequences from Xiangshan Bay populations compared with those of other populations showed that most molecular variance was within groups, which was consistent with the low pairwise FST values. The neutrality test revealed that C. sikamea experienced population expansion events, whereas for C. angulata, the significant Fu's Fs and non-significant Tajima's D test results may indicate a possible population expansion event, implying that C. sikamea is likely the indigenous species. The method established based on ITS1 (internal transcribed spacer 1) digestion by the Hind III restriction enzyme is useful for identifying C. sikamea and C. angulata in the local region. The specific primers on the MNR sequence show potential for distinguishing C. sikamea from four other important Crassostrea oysters. These results highlight the abundance of C. sikamea in the Zhejiang coast and lay the foundation for protecting and utilizing the local oyster germplasm resources and for the sustainable development of the oyster industry.